(untitled) (UNWE Yearbook, 2024)
The article proposes the incorporation of travel writing as a linguistic resource in teaching English for specific purposes (ESP). Introducing generic variety into a language lesson is supported by the principles of communicative language teaching. Travel writing is also proven to be both a vehicle of relevant content and a powerful stimulus for students´ involvement in the lesson. Taking social constructivism as its second vector, the article discusses travel writing as a mediatized resource for making sense of the world. Recent publications of travel experiences in Bulgaria are read through the lens of critical discourse analysis seeking to identify travellers´ levels of engagement with the Bulgarian heritage. Focus on the construction of Bulgarian heritage could stimulate critical thinking by alerting students to the fact that communication is never innocent of ideology and travelogues are often instrumental in popular geopolitics.